2017
DOI: 10.14393/bj-v33n4a2017-36986
|View full text |Cite
|
Sign up to set email alerts
|

A fourteen-year retrospective of clinic-epidemiological aspects of cutaneous and visceral leishmaniasis in Uberlândia, Minas Gerais, Brazil

Abstract: ABSTRACT:The purpose of this study was to describe clinic-epidemiological characteristics of leishmaniasis cases attended at the Clinical Hospital of Federal University of Uberlândia (CHU), state of Minas Gerais, from January 2000 to December 2013. This is a descriptive and retrospective review of medical records of patients diagnosed with leishmaniasis and treated at the CHU. 168 cases of leishmaniasis were analyzed and most patients were male, aged 23 to 60 years. For cutaneous and mucosal leishmaniasis, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…(2,0%) notificações respectivamente (Figura 1). A diversidade e ampla distribuição geográfica da fauna flebotomínea no estado de Pernambuco, contribui para a transmissão da LV (BRITO et al, 2012;SILVA et al, 2017) Com relação ao número de casos notificados por sexo é possível observar que para a maioria das doenças estudadas houve predomínio do sexo masculino, com prevalência de 69,5% para LV, 65,6% para LTA e 55,6% para malária (figura 2), corroborando com estudos realizados anteriormente, nos quais indicam que os homens representam o maior percentual de infectados por serem mais expostos em suas atividades diárias (VASCONCELOS et al, 2017;SILVA et al, 2021;ARAÚJO;NUNES, 2017;BRAZUNA et al, 2012;FARIA et al, 2019).…”
Section: Resultados E Discussõesunclassified
“…(2,0%) notificações respectivamente (Figura 1). A diversidade e ampla distribuição geográfica da fauna flebotomínea no estado de Pernambuco, contribui para a transmissão da LV (BRITO et al, 2012;SILVA et al, 2017) Com relação ao número de casos notificados por sexo é possível observar que para a maioria das doenças estudadas houve predomínio do sexo masculino, com prevalência de 69,5% para LV, 65,6% para LTA e 55,6% para malária (figura 2), corroborando com estudos realizados anteriormente, nos quais indicam que os homens representam o maior percentual de infectados por serem mais expostos em suas atividades diárias (VASCONCELOS et al, 2017;SILVA et al, 2021;ARAÚJO;NUNES, 2017;BRAZUNA et al, 2012;FARIA et al, 2019).…”
Section: Resultados E Discussõesunclassified
“…In another study in Minas Gerais (SILVA, 2017), cases of VL were initially treated with antimonial and replaced with amphotericin B (deoxycholate or liposomal) in the event of therapeutic failure. Araújo and Nunes (2017) observed that the most used treatment for TL in the cutaneous and mucosal forms was glucantime, alone or in combination with pentoxifylline, while treatment for VL was performed with amphotericin B or glucantime. In the present study, all victims were cured.…”
Section: Resultsmentioning
confidence: 99%